Pediatric Fracture Epidemiology in an Orthopaedic Urgent Care Setting - Alexandra Abbott, MD; Kate Swertfager, BS; Summer Bloom, ATC; Nicholas J. Jackson, PhD, MPH; Joshua Goldman, MD, MBA (Journal of the Pediatric Orthopaedic Society of North America)
Background: Epidemiological data for pediatric fracture are limited, especially specific to the United States. Recent cohort studies from emergency departments and orthopaedic surgery clinics potentially skew data to more severe diagnoses. This retrospective cross-sectional study aims to update the epidemiology of pediatric fracture patients who presented to a pediatric orthopaedic urgent care center in an urban location. Methods: A total of 61,345 pediatric patients presented to an orthopaedics-focused urgent care from April 2019 to February 2023, and we analyzed data from 38,336 patients who received primary diagnoses of one or more fractures. Data were analyzed for associations between diagnoses and injury sites with age group, date of service, and sex. Results: Among more comprehensive epidemiological results, the mean age of patients with fractures was 9.7 years ± 4.3. Of the patients, 13,918 (36%) were female and 24,559 (64%) were male. School-aged children (aged 6 to 11 years) and adolescents (aged 12 to 18 years) each represented 40% (collectively 80%) of patients with fracture diagnoses. The most common fracture sites were of the wrist (27%), hand (18%), elbow (14%), and foot (12%). The most commonly injured bones were the radius (30%), hand phalanx (14%), and humerus (10%). Fracture subtype distribution included torus (13%), Salter-Harris (9%), avulsion (1%), and greenstick (less than 1%). Conclusion: This cohort study demonstrates disproportionate fracture presentation in males and in school-aged children (aged 6 to 12 years) and in adolescents (aged 12 to 18 years). We also demonstrate that radius and hand phalanx fractures are the most common in our pediatric cohort, together representing nearly half of fracture diagnoses. Key Concepts: (1) This study provides comprehensive and precise characterization of demographics and associations with pediatric fractures. (2) This cohort, from a high-volume pediatric orthopaedic center, contributes robust and specific diagnostic data to improve upon prior studies’ characterization of epidemiology. (3) Epidemiological characterization is important for guiding curriculums for clinician training, imaging pretest probabilities for various fracture diagnoses, and risk assessments based on demographics and injury sites. Level of Evidence: Level IV